Estratégia, competências e performance das empresas de software paranaenses - Gava Neto, José (2009)
This study deals with composition of software industry of Parana State and its purpose is to investigate how is the adopted strategy to face the environment, to identify enterprise’s competences and performance. The research problem is to find the relations between strategies, competences and performance of software industry enterprises in Parana State. It is about a applied research of exploratory and descriptive nature, as quantitative and inductive. Data are collected through surveys that were built upon semi-structured interviews with entrepreneurs and leaders of software industry entities and validated instruments of others authors. Data analysis has been made using statistic multivariate analysis called Factorial Analysis and after this was used Pearson correlation coefficient to analyze relations between variables. The results of the research evidences there is significance relations between variables, as well as describes segments of software industry like as their profiles, environment, strategic typologies, competences and performance. The characteristics of software industry environment are complexity and predictable, dynamic market, however, it has few possibilities of growth, because there are few resources and growing niches, according entrepreneurs’ perceptions. The prospectors businesses are majority, which is the most adopted in each segment of software sector, followed by analytic tipologie. About competences, the software sector has biggest competences on business management and technical competences. The strongest correlations were founded between competences and performance, standing out the correlation between Management and Customers Results and Business Management competences. Both compentences and performance showed significatives correlations between them, ie, competences showed correlated with performance (who has management competence tends to have technical and marketing competences), and in the expected direction (business with more installed competences tend to have best percept performance). At last suggestions and recommendations are been presented about future studies on the software industry as: to extend the sample beyond of participating companies of APL's Paraná, thus allowing a more general vision of the sector; to investigate separately each of the segments of the Parana State software aiming to be a indepth knowledge of each segment, the use of other instruments methodological or theoretical references for the characterization of the strategies adopted by companies, the application of multivariate statistical technique cluster analysis to identify companies that are similar with a comparative analysis of their performances and competences, which could expand the perception about the sector..